Space ranger to the rescue - Bouchard, Natasha; Disney Storybook Artists (2022)
Based on Disney/Pixar Lightyear movie, tells the origin story of Buzz Lightyear, revealing how a young test pilot became a space ranger.
At head of title: Disney · Pixar: Lightyear.
Keywords: Lightyear, Buzz -- (Fictitious character) -- Juvenile fiction; Lightyear, Buzz -- (Fictitious character); Air pilots -- Juvenile fiction; Astronauts -- Juvenile fiction; Toys -- Juvenile fiction; Manned space flight -- Juvenile fiction; Interplanetary voyages -- Juvenile fiction; Picture books; JUVENILE FICTION / Media Tie-In.; JUVENILE FICTION / Toys, Dolls & Puppets; JUVENILE FICTION / Science Fiction; Air pilots; Astronauts; Interplanetary voyages; Manned space flight; Toys; Readers; Children's stories; Fiction; Juvenile works; Picture books; Readers (Publications); Readers (Publications); Picture books